Yurchenko I .V On The Existence Of Optimal Control For Stochastic Differential Functional Equations Under The Influence Of External Disturbances // International Scientific Conference "Organization of Scientific Research in Modern Conditions‘2025". Conference Proceedings. Series Conference proceedings «SW-Us conference proceedings». March, 2025.– ProConference in conjunction with KindleDPSeattle, Washington, USA. - Yurchenko, Igor Valeryjovych (ProConference in conjunction with KindleDPSeattle, Washington, USA., 2025)
The article discusses the comparison theorem for solutions of stochastic differential functional equations under the influence of external disturbances and its application to one problem of stochastic control.
The article discusses the comparison theorem for solutions of stochastic differential functional equations under the influence of external disturbances and its application to one problem of stochastic control.
Keywords: comparison theorem; stochastic control; stochastic functional differential equations